Analisis Atribut Produk Dalam Keputusan Pembelian Di Toko Murni Baru - Hartanto, Bobby; Effendi, Hafizah; Damanik, Sri Winda Hardiyanti (Management And Business Progress, 2024)
This study aims to determine the effect of product attributes on purchasing decisions at Murni Baru Stores. The research method used is a quantitative method using the help of SPSS version 25.00 which was collected from the results of distributing questionnaires via Google Form to 75 respondents. The analytical method used in this study is the instrument test, namely the validity and reliability test. Classic assumption test, namely normality test, multiple linear regression analysis, analysis of the coefficient of determination (R2) and hypothesis testing. The results of SPSS in this study were variables product quality (X1) affecting purchasing decisions (Y), variables design’s product (X2) do not influencing purchasing decisions (Y), variables brand’s product (X3) do not influencing purchasing decisions (Y), Variable product support service influences the purchasing decision (Y), variable price’s product do not influencing purchasing product. The influence of product quality, product design, product brand, product support services and product prices on purchasing decisions at Murni Baru Stores is indicated by a coefficient of determination of 0.860. This shows that 86% of purchasing decisions are influenced by product quality (X1), Product design (X2), product brand (X3), product support services (X4) and product price (X5) and the remaining 14% are influenced by other variables which are not used in this study.